2022
DOI: 10.3390/s22062079
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Rate Estimation from Head-Worn Photoplethysmography Sensor Data Using Machine Learning

Abstract: Breathing rate is considered one of the fundamental vital signs and a highly informative indicator of physiological state. Given that the monitoring of heart activity is less complex than the monitoring of breathing, a variety of algorithms have been developed to estimate breathing activity from heart activity. However, estimating breathing rate from heart activity outside of laboratory conditions is still a challenge. The challenge is even greater when new wearable devices with novel sensor placements are bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For data collection, we used the emteqPro device 20 – 22 . The device comprises a facial electromyographic (EMG), a photoplethysmographic (PPG), and an inertial measurement unit (IMU) sensor integrated within a soft frame that fits on the face of the wearer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For data collection, we used the emteqPro device 20 – 22 . The device comprises a facial electromyographic (EMG), a photoplethysmographic (PPG), and an inertial measurement unit (IMU) sensor integrated within a soft frame that fits on the face of the wearer.…”
Section: Methodsmentioning
confidence: 99%
“…This study investigates the association between facial sEMG and subjective and objective affect, using a novel wearable sEMG sensing device in VR environments. We used a set of dry, arrayed sEMG sensors (emteqPro) 20 – 22 , attached to a Pico Virtual Reality (VR) headset. During the experiments, physiological recordings and subjective self-reported data were collected from participants following exposure to videos varying in arousal and valence.…”
Section: Introductionmentioning
confidence: 99%
“…Birrenkott et al [ 8 ] used ML algorithms such as random forest regression, support vector regression, etc., to create a smart fusion that fuses the RR obtained from different modulations of ECG and PPG. An ML-based approach to extract RR from headworn PPG was presented by [ 30 ]. Chan et al [ 11 ] used linear regression to fuse the respiration signal obtained from ECG and accelerometer.…”
Section: Related Workmentioning
confidence: 99%
“…According to relevant reports, the breathing rate of healthy and normal adults is ≈12-20 times per minute, and the breathing rate is 12-18 times in a resting state, when the breathing exceeds this range, it means that your physical state may be in an unhealthy and uneasy state. [41,42] Figure 4d imitates the beard of the human body, put the P-silk/RG e-skin under the nose of the human body, and monitors the respiratory state and air exchange frequency changes of the same human body in a healthy state and a sick state. The results showed that the breathing intensity of the human body in the sick state was lower than that in the healthy state, but the breathing rate increased (from 18 times min −1 to 23 times min −1 ).…”
Section: Application Of Different Forms Of P-silk/rg Electronic Skin ...mentioning
confidence: 99%